Análise das características de infraestrutura e acidentalidade viária em cruzamentos críticos da cidade de Uberlândia, MG - Souza, Paola Mundim de (2016)
Due to the increased number of fatal crashes, the decade from 2011 to 2020 was defined as the Decade of Road Safety, which ended in the drafting of the National Plan to Reduce Accidents and Road Safety, which proposes actions that are based on five issues, one of then the infrastructure. This thesis aimed in analyzing the influence that the infrastructure characteristics have on road safety and to check the evolution of the incidence and severity of accidents over the years. Traffic accident data were analyzed on some streets of Uberlândia, MG, and the infrastructure characteristics, that is, the current geometry and what changes were implemented in recent years. By calculating the Pearson’s coefficient, it was verified if there were a correlation between variation in the number of accidents with severity, changes in the road infrastructure, and variation of vehicular flow. In general, changes in the infrastructure of the analyzed streets, such as increased the number of lanes of traffic, reduced speed limit, construction of overpasses, and structural bus corridor deployment caused a decreasing in the number of accidents and severity.